An automated radiotelemetry system (ARTS) for monitoring small mammals. Issue 5 (26th March 2022) - Wallace, Gerard; Elden, Marija; Boucher, Rachel; Phelps, Steven
Abstract: The study of animals in nature is essential for developing an ecologically valid understanding of behaviour. Small mammals, however, are often fossorial and exceedingly difficult to monitor in the wild. This limits both the taxonomic scope of field observation, and excludes species that are powerful models for the study of behavioural mechanisms. Here, we implement an automated radiotelemetry system (ARTS) designed to track small fossorial mammals. Our ARTS uses an isotropic antenna array coupled with broadband receivers. We characterized transmission at our study site and tested the ARTS's ability to track 48 prairie voles. We compared position estimates from nonlinear least squares, nonparametric and Bayesian trilateration methods and found Bayesian trilateration to have the smallest error. To examine the ability of the system to track biologically significant behaviour, we used ARTS data to investigate circadian rhythms of freely behaving prairie voles. We used Lomb–Scargle analysis to estimate periodic patterns from irregularly sampled time series. Prairie voles demonstrated circadian and ultradian movement. This ARTS offers a new tool to observe rodent behaviour at time‐scales and in environments that have not been previously possible, such as investigating social and spatial behaviours on the scale of minutes, hours and days in natural environments.